STUDI ANALISIS AL-MUROBBA' DALAM PENENTUAN AWAL WAKTU SHALAT ASHAR - Zar'ah, Nur Fajriani Zar'ah; Anwari, Fiqhi Ikhsan (ELFALAKY: Jurnal Ilmu Falak, 2023)
This study was motivated by the researcher's attention to the beginning of the Asr prayer time, which in its determination requires high accuracy and a long formula. Because in determining the beginning of the 'Asr prayer time, the height of the Sun must be found first using the Sun's height formula. So a tool is needed that is easier to determine the beginning of the Asr prayer time without very long calculations, namely Al-Murobba'. Thus the focus of this study is to find out the accuracy of Al-Murobba' in determine the beginning of Asr prayer time. This research is categorized as field research with a descriptive qualitative approach. The sources and types of data used are Al-Murobba' instruments and several books, articles and scientific journals that are in accordance with the research theme. While the analysis uses data reduction, data presentation and conclusion writing. The results of this study indicate that Al-Murobba' has accuracy is categorized as quite accurate. This is evidenced by the results of the researcher's observations 5 (five) times by comparing the results using the spherical trigonometry calculation method. The time gap which is shown in Al-Murobba' and spherical trigonometry is 0-2 minutes.